Epidemiology and clinics of mushroom poisoning in Northern Italy: A 21-year retrospective analysis. (July 2018) - Cervellin, G; Comelli, I; Rastelli, G; Sanchis-Gomar, F; Negri, F; De Luca, C; Lippi, G
Background: Limited information exists about epidemiology and management of mushroom poisoning. We analyzed and described epidemiology, clinical presentation, and clinical course of mushroom-poisoned patients admitted to emergency departments (EDs) of the Province of Parma, Italy. Methods: Data from the database of mycological service were matched with clinical information retrieved from hospitals' database, from January 1, 1996 to December 31, 2016. Results: Mycologist consultation was obtained in 379/443 identified mushroom poisonings. A remarkable seasonality was found, with significant peak in autumn. Thanks to the collaboration, the implicated species could be identified in 397 cases (89.6%); 108 cases (24.4%) were due to edible mushrooms, Boletus edulis being the most represented (63 cases). Overall, 408 (92%) cases presented with gastrointestinal toxicity. Twenty cases of amatoxin poisoning were recorded (11 Amanita phalloides and 9 Lepiota brunneoincarnata ). One liver transplantation was needed. We observed 13 cases of cholinergic toxicity and 2 cases of hallucinogenic toxicity. Finally, 46 cases were due to "mixed" toxicities, and a total of 69 needed hospitalization. Conclusions: Early identification and management of potentially life-threatening cases is challenging in the ED, so that a mycologist service on call is highly advisable, especially during periods characterized by the highest incidence of poisoning.